Kepuasan Kerja Karyawan pada Perusahaan - Sari, Alma Diva; Dewi, Ira Kesuma (Tabularasa: Jurnal Ilmiah Magister Psikologi, 2025)
This research aims to determine the factors that influence employee job satisfaction. Data collection in this research was by reviewing 15 relevant literature to determine the factors that influence employee job satisfaction. The type of research used is a literature study. Where researchers rely on various literature to obtain research data and use a qualitative approach because the data produced is in the form of words or descriptions. The conclusion drawn from the study found by researchers is that leadership factors, work environment, compensation, and job training influence employee job satisfaction. As an employee, you must also pay attention to the work productivity you want to achieve, so this will certainly have an indirect influence on employee job satisfaction